MORINGA OLEIFERA (MO) SEED SHELL BASED ADSORBENT FOR POTENTIAL CO2 CAPTURE: A CHARACTERIZATION STUDY - Amina Tahreen,; Mohammed Saedi Jami,; Fathilah Ali,; Zahangir Alam, (Malaysian Journal of Science, 2024)
This study characterizes activated carbon synthesized from Moringa oleifera (MO) seed husk with a greener activating agent, namely sodium carbonate, (Na2CO3) compared to traditional activating agent, potassium hydroxide (KOH). Synthesized in a conventional tube furnace with nitrogen supply, the resulting activated carbon after cooling and washing, were characterized for Brunauer-Emmett-Teller (BET), Fourier-Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD) and Scanning Electron Microscope (SEM) analyses and compared with that produced with KOH activation. Although fewer and larger mesoporous activated carbon with smaller BET surface area (18.4659 m²/g) were formed with Na2CO3 activation), compared to that of KOH activation (235.6034 m²/g), this study highlights the ability and potential of the greener activating agent (Na2CO3) to utilize biomass waste and successfully produce activated carbon with minimum environmental hazards. The synthesized adsorbent can be explored for CO2 capture applications in future studies.